Effect of reservoir boundaries on the seismic response of gravity dams - Hatami, Kianoosh (My University, 1997)
Dam safety is an important issue of current interest. In seismic regions, dynamic forces on the dam may be significant and may lead to crack initiation and propagation in the dam. A significant component of the dynamic forces is due to the hydrodynamic effects of the impounded water in the reservoir. The developed hydrodynamic force on the dam is highly dependent on the physical characteristics of the boundaries surrounding the reservoir including the reservoir bottom and sides. In this study, the effects of the reservoir boundary conditions on the seismic response of the dam are investigated. This study consists of four components. First, a mathematical model is proposed to account for the absorption effect of a sedimented reservoir bottom on the seismic response of the dam-reservoir system. Secondly, a study is conducted to examine the possibility of reducing the earthquake response of concrete gravity dams using hydrodynamic isolation at the dam-reservoir boundary. Thirdly, an analytical procedure is developed to compute the response of the hydrodynamic pressure and the seismic response of the dam impounding a reservoir of general shape and boundary conditions. Finally, the earthquake response of the dam was studied with special attention to the stresses in the dam. An index for the evaluation of the overall state of stress in the dam subjected to different load combinations is proposed. The dynamic component of stress and the proposed index in the dam are computed when the dam-reservoir system is subjected to different ground motion records. The effect of the reflected waves from underlying reservoir foundation rock on the calculated response of the dam when subjected to earthquake ground motion was found to be very important. It is concluded that the effect of the stiffness of a semi-infinite reservoir foundation on the reduction of the dam seismic response is more significant as compared to the dissipation effect of the sedimentation layer. It is shown that the isolation layer needs to be very soft and with sufficient thickness so as to effectively reduce the hydrodynamic pressure acting on the dam. The effects of the reservoir length and the type of boundary condition at the truncated reservoir boundary on the calculated response of hydrodynamic pressure were found significant. The proposed index for the stress in the dam (Stress Factor) was shown to have an acceptable correlation with the intensity of the input ground motion and can be used as a complementary design factor for seismic design of concrete gravity dams.
Keywords: Civil Engineering; Civil Engineering